Metastatic castration-resistant prostate cancer (mCRPC) treated with 225Ac-PSMA-617. Case report - Medeiros, Rodrigo Bovolin de; Grigolon, Marcus Vinicius; Araújo, Tatianny Paula; Srougi, Miguel (Brazilian Journal of Oncology, 2019)
Metastatic castration-resistant prostate cancer (mCRPC) is an extremely severe disease that relentlessly evolves to death. Over the past few years, we have seen significant improvements in the different types of treatments available, which have positively impacted several clinical outcomes, including higher survival rates and better quality of life. Since Radium-223 approval by FDA in 2013, nuclear medicine has been incorporated to the therapeutic arsenal. Progress in this field have motivated a pursuit for new targeted therapies using radioactive isotopes. Recent reports addressing the first cases treated with this technique are impressive due to the high response rates obtained in refractory patients. Here we report the case of a patient with mCRPC who had been previously treated with several lines of anti-androgen therapy and cytotoxic chemotherapy, recently treated with PSMA labeled with the alpha-emitting radioisotope Actinium-225 (225 Ac).
Keywords: Prostatic Neoplasms; Castration-Resistant; Nuclear Medicine; Alpha Particles